MYC and gastric adenocarcinoma carcinogenesis - Calcagno, Danielle Queiroz (The WJG Press and Baishideng, 2008)
MYC is an oncogene involved in cell cycle regulation, cell growth arrest, cell adhesion, metabolism, ribosome biogenesis, protein synthesis, and mitochondrial function. It has been described as a key element of several carcinogenesis processes in humans. Many studies have shown an association between MYC deregulation and gastric cancer. MYC deregulation is also seen in gastric preneoplastic lesions and thus it may have a role in early gastric carcinogenesis. Several studies have suggested that amplification is the main mechanism of MYC deregulation in gastric cancer. In the present review, we focus on the deregulation of the MYC oncogene in gastric adenocarcinoma carcinogenesis, including its association with Helicobacter pylori (H pylori) and clinical applications.